Accelerated curing and strength of soil−cement mixtures - Endo, Munehito; Komiya, Kazuhito; Yamanobe, Junichi; Shiozawa, Takuya (Japanese Geotechnical Society Special Publication, 2015)
In situ soil-cement mixing is frequently used to minimize soil liquefaction, enhance soil strength and reduce soil permeability. For quality assurance purposes, drill core samples are taken from the soil-cement mixtures and unconfined compressive strength tests are carried out 28 days after mixing and placement, which may delay construction works. Clearly, there is a need to accurately predict the strength of soil-cement mixtures early. In this study, we prepared soil-cement mixtures with different proportions of clay, silt, sand, cement and water. The as-prepared specimens were subsequently cured at standard and various temperature, pressure and time conditions. We then compared the strength characteristics of the as-prepared soil-cement specimens. Unconfined compressive strength increases between 24 h and 48 h of accelerated curing; however, increasing the curing temperature does not lead to increases in strength. Compressive strength slightly increases with the curing pressure. Finally, the compressive strength depends on the cement and fines content and WTotal/C of the soil-cement mixtures.